2000
DOI: 10.1046/j.1365-2621.2000.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of industrial processed milk by analysis of heat‐induced changes

Abstract: Thermal indicators in milk, which had been subjected to one of the six industrial processes of thermization, pasteurization, direct and indirect UHT-sterilization, pre-sterilization and in-bottle sterilization, were studied. The following three indices of heat damage were analyzed by high performance liquid chromatography (HPLC), hydroxymethylfurfural (HMF), lactulose and acid-soluble ␤-lactoglobulin(␤-LG). Average amounts found were 1710 mg/L of ␤-LG and 2.49 mol/L of HMF in pasteurized milk. In UHT milk, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 14 publications
7
66
1
5
Order By: Relevance
“…The relative standard deviation (RSD) was 1.91% obtained on a UHT milk sample with an average β-Lg content of 339.9 ± 6.5 mg·L −1 milk, and 0.26% on an ESL milk sample (2397.8 ± 6.2 mg·L quality is demonstrated in Figure 2. Compared to the results obtained by other authors [14,21], a faster separation and a much more stable baseline were the most striking advantages of the HPLC column used in the present study.…”
Section: Rp-hplc Analysis Of Acid-soluble β-Lactoglobulin In Milk Samcontrasting
confidence: 49%
“…The relative standard deviation (RSD) was 1.91% obtained on a UHT milk sample with an average β-Lg content of 339.9 ± 6.5 mg·L −1 milk, and 0.26% on an ESL milk sample (2397.8 ± 6.2 mg·L quality is demonstrated in Figure 2. Compared to the results obtained by other authors [14,21], a faster separation and a much more stable baseline were the most striking advantages of the HPLC column used in the present study.…”
Section: Rp-hplc Analysis Of Acid-soluble β-Lactoglobulin In Milk Samcontrasting
confidence: 49%
“…3), it is possible that other flavor defects such as bitterness may have been detectable at the end of the shelf life, as indicated by the presence of sweet curdling in some of the studied samples. No changes on the sensory characteristics of the product due to the applied thermal or nonthermal treatments were observed, or expected, based on the findings by Morales, Romero, and Jimenez-Perez (2000), and Qin et al (1995a). Microbiological screening of the treated samples for pathogenic bacteria demonstrated that all treated samples were free of Salmonella spp., Listeria monocytogenes and Bacillus cereus, which are thermoduric pathogenic bacteria with the potential to grow at refrigeration temperatures that may cause health concerns if present in milk (Collins-Thompson & Bunning, 1992).…”
Section: Resultsmentioning
confidence: 68%
“…Nowadays, various systems and technologies associated with different time-temperature profiles have been developed to obtain pasteurized and ultra-high temperature (UHT) milk, and the effect on the nutritional and sensory quality of commercial milk samples may vary substantially depending on the process (Awad, 2006;Morales, Romero, & Jimenez-Perez, 2000). For regulatory purposes, attention should be paid to evaluate the authentication of heat-treated milks and milk integrity since heat treatments change the biochemical composition of milk.…”
Section: Introductionmentioning
confidence: 99%